Differential Superiority of Heavy Charged-Particle Irradiation to X-Rays: Studies on Biological Effectiveness and Side Effect Mechanisms in Multicellular Tumor and Normal Tissue Models - Walenta, Stefan; Mueller-Klieser, Wolfgang (Frontiers in Oncology, 2016)
This review is focused on the radiobiology of carbon ions compared to x-rays using multicellular models of tumors and normal mucosa. The first part summarizes basic radiobiological effects, as observed in cancer cells. The second, more clinically oriented part of the review deals with radiation-induced cell migration and mucositis. Multicellular spheroids (MCS) from V79 hamster cells were irradiated with x-rays or carbon ions under ambient or restricted oxygen supply conditions. Oxygen enhancement ratios (OER) were 2.9, 2.8, and 1.4 for irradiation with photons, 12C+6 in the plateau region, and 12C+6 in the Bragg peak, respectively. A relative biological effectiveness (RBE) of 4.3 and 2.1 for ambient pO2 and hypoxia was obtained, respectively. The high effectiveness of carbon ions was reflected by an enhanced accumulation of cells in G2/M, and a dose-dependent massive induction of apoptosis. Clinically relevant doses (3 Gy) of x-rays induced an increase in migratory activity of U87 but not of LN229 or HCT116 tumor cells. Such an increase in cell motility following irradiation in situ could be the source of recurrence. In contrast, carbon ion treatment was associated with a dose-dependent decrease in migration with all cell lines and under all conditions investigated. The radiation-induced loss of cell motility was correlated, in most cases, with corresponding changes in 1 integrin expression. Unlike with particles, the photon-induced increase in cell migration was paralleled by an elevated phosphorylation status of the epidermal growth factor receptor (EGFR) and AKT-ERK1/2 pathway. Comparing the gene toxicity of x-rays with that of particles using the gamma-H2AX technique in organotypic cultures of the oral mucosa, the superior effectiveness of heavy ions was confirmed by a two-fold higher number of foci per nucleus. Pro-inflammatory signs, however, were similar for both treatment modalities, e. g., the activation of NFkappaB, and the release of IL6 and IL8. In summary, particle irradiation is superior to gamma-rays due to a higher radiobiological effectiveness, a reduced hypoxia-induced radioresistance, a multicellular radiosensitization and the absence of a radiation-induced cell motility. The potential of inducing mucositis, however, is similar for both radiation types.